The effectiveness of edutainment in teaching cell cycle and transport mechanisms - Litera, Emman A.; Bulay, Minie L. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Traditional lecture-based teaching methods prevalent in Philippine schools often lead to passive learning. By contrast, this study investigates the active engagement and enhanced conceptual comprehension facilitated by edutainment through Classcraft v.4.2.6, focusing on the least learned competencies of cell cycle and transport mechanisms. Expert evaluation of edutainment content affirmed its potential as a valuable educational tool. Students exposed to the edutainment method showed significantly improved learning outcomes compared to those taught via traditional lecture method, as validated by statistical analyses. However, challenges such as technological barriers and distractions were acknowledged. To optimize edutainment’s benefits, strategic design considerations and support mechanisms are recommended, including purposeful design, progressive complexity, and educator training. This study significantly updates knowledge in educational practices by highlighting edutainment’s efficacy. By challenging lecture-based teaching, it advocates for more engaging instructional approaches in Philippine secondary education, promising enhanced learning experiences and outcomes.